Healthy Living: High Blood Pressure - Linda B. Bobroff; Leigh Ann Martin (EDIS, 2009)
Revised! FCS8599, a 1-page illustrated handout by Linda B. Bobroff and Leigh Ann Martin, explains what high blood pressure, or hypertension, is, risk factors, and encourages regular blood pressure check-ups. Published by the UF Department of Family Youth and Community Sciences, October 2009.